Challenges in the diagnosis and management of interstitial and cornual ectopic pregnancies - Botros Rizk; Candice P. Holliday; Mostafa Abuzeid (Middle East Fertility Society Journal, 2013)
Interstitial ectopic pregnancy is a term loosely used in the literature to describe three different entities. The first is the true interstitial ectopic pregnancy, which occurs in the interstitial or intramural segment of the Fallopian tubes. The term cornual ectopic pregnancy should be reserved for pregnancy in women with a single uterine horn, a bicornuate uterus, or a septate uterus. Angular pregnancy is a term that is rarely used and should be limited to a pregnancy in one of the angles of the uterus, but not inside the Fallopian tube. Historically, interstitial pregnancy was considered safe to manage conservatively until over 12 weeks because of the delayed risk of rupture as a result of the protection offered by the muscle of the uterus. However, over the last decade evidence now suggests that early rupture is not uncommon. The management of an interstitial pregnancy should be ascertained by ultrasonography, particularly three-dimensional ultrasonography. Depending on the size and viability of the pregnancy, management should be planned accordingly. Laparoscopic management is ideal for surgeons comfortable with the principles of laparoscopic surgery and suturing. However, laparotomy is a suitable alternative that will always provide a safe outcome. Adequate suturing of uterine cornua could prevent the risk of rupture during subsequent pregnancies. Minimizing blood loss during and after surgery is a priority.